Role Of Forensic Science In The Criminal Justice System - Abrol, Chahat (Trinity Law Review, 2021)
With all the growth and development in the society, crime and criminals present themselves in ingenious forms and novel modes. Thus, the manoeuvre of modern forensic techniques is seminal to effective criminal investigative and judicial process. The use of techniques such as DNA related testing, lie-detector test, brain-mapping and narco-analysis helps in deciding the case. This article aims to throw light upon the type of techniques that are utilised in forensic analysis and how forensic science is applied to different laws and statues in the country. The paper also tries to find the question as to whether different areas of forensic science like narco-analysis and brain mapping infringe the fundamental rights of the accused such as the right against self-incrimination under Article 20(3) of the Constitution, privacy and health of the accused. Also, the article delineates the different classes of cases in which forensic science is used, especially establishing the corpus delicti, identification of the instrument of crime, nature of injuries, fingerprints and DNA testing.